(3cJGH GdeZfjSjGs - (3GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO, CHh ESeGYjd, eDjO GdOjf, GdCUHgGfj GdWZQGFj,J (B513 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO GSYOc Gddg HWGYJg abGd YReJ bGFd jDJi GdMceI ef jTGA hef jDJi GdMceI abO ChJi NjQkG cKjQkG s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg EPG GNJdWJ HCLRGA GdLSe dGjecf GdJejjR HjfgeG aJUjQ eG jYO ef GdeRGL eG LRI Yf GdJeGS hdPdc bGdhG Ydjce HGdeJab hEjGce hGdeNJda aGf GdeNJda dG jCJda Ydi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs